Does my patient have heart failure? - Carlos Buso (Revista de la Sociedad Argentina de Diabetes, 2022)
Heart failure (HF) is a common entity in the world with a global prevalence of 1-2% of the general probability that increases with greater chronological age and the presence of classic risk factors (hypertension, dyslipidemia, cardiovascular disease, obesity, arrhythmias, etc.) and specific risk factors for women (eclampsia, polycystic ovary, microvascular injury pattern, etc.). Diabetes mellitus (DM) is a spreading disease and plays an early role in the pathogenesis of atherogenesis and cardiac structural changes that determine a two and a half times higher prevalence of HF, and an increased signal of early mortality by direct mechanisms. associated with cardiac structural damage (myocardiocyte-interstitium-collagen support) or vascular alterations, multivessel, multistage, multiorgan.